Praktik Botoh pada demokrasi lokal: Studi pada pemilihan Bupati Lamongan 2020 - Susilowati, Ana Dewi Lanjar Diwuk; Fitrianto, Hari (Universitas Airlangga, 2024)
This study examines the practice of botoh in the 2020 Lamongan regent election. The phenomenon of vote buying and the high potential for money politics in a region have triggered various practices of money politics in local elections. This research uses a descriptive qualitative approach. Data collection was carried out through in-depth interviews, with both primary and secondary data types. The aim of this study is to understand the practice and patterns of botoh in the 2020 Lamongan election and to determine how botoh influences voter preferences. The results indicate that the practice and working patterns of botoh in the 2020 Lamongan election were conducted in two ways. First, purely for material gain, involving bets among botoh practitioners. Second, as part of a candidate's campaign team, with a more systematic working mechanism. Botoh significantly influenced voter preferences in the 2020 Lamongan election, particularly in the southern region. The population in this area, classified as 'Abangan' and accustomed to the culture of money politics, was easily influenced by botoh practices.